New Isotope Evidence for Diachronic and Site-Spatial Variation in Precontact Diet during the Little Ice Age at Nunalleq, Southwest Alaska - Britton, Kate (Études Inuit Studies, 2019)
The stable isotope analysis of preserved proteinaceous tissues, such as bone collagen and hair keratin, offers a powerful means of examining individual dietary practices in archaeology and, through this, inferring the subsistence behaviours, socio-cultural practices, and food preferences of past populations. Previous isotope research at the precontact Yup’ik village site of Nunalleq, Alaska, has provided evidence of a mixed diet of marine and terrestrial foods (but likely dominated by salmonids), but also highlighted some dietary variability amongst the inhabitants of the site. However, materials from the older rescue excavations were insufficient to infer whether this variability was interpersonal and/or diachronic in nature. Here, new stable carbon and nitrogen isotope data from human hair are presented. These were obtained during the research excavations at Nunalleq from temporally constrained, well-stratified contexts. The new data reveal dietary change through time at the site, highlighting changes in resource use and subsistence practices during the Little Ice Age. During the middle phase of occupation at the site (Phase III; cal AD 1620–1650), diet is more varied, most likely relating to the differing relative contribution of salmon versus higher trophic level marine mammal protein to the diet of some individuals at the site. Analysis reveals these differences to be site-spatial, possibly indicating differences with the use of space at the site, and/or hinting at possible social differentiation in diet during Phase III. In the final occupation phase (Phase II; cal AD 1640–1660), diet is more homogeneous and demonstrates an increased exploitation of higher-trophic level marine foods.